A Critical Study of Tax Assessment in Nagarpalika of Amravati District - Bele, Dinesh Prabhakarrao; Pimple, Manoj M (Journal of Commerce and Trade, 2018)
The income from Tax is considered asaimportant revenue. However, this income sources is important as per our Indian constitution in representative democracy, But the use of taxes income for development is not satisfactory. The action which Government takes on the basis of collected tax is not social beneficial. The process of spending money on various project is doubtful and also corrupted. So this tax assessment is made compulsory by low constitution as per 40 direction constituted in 1949. This study will be focus on the process of Tax collection and assessment in various Nagarpalikas of Amravati District. It is an honest attempt to find out the various method of tax assessment as well as implementation of collected money for social development. Classification-JEL : H21, H22, H27, H31, H71